Prigionieri di guerra ungheresi in Sicilia dopo la prima guerra mondiale - Keglovich, Rita (Verbum – Analecta Neolatina, 2005)
The study discusses the everyday life of Hungarian prisoners of war during and after World War I. The paper first presents a brief historical summary, then discusses the number of the Hungarian p.o.w.'s in Italy, with a special focus on Sicily, as well as prison camps in Vittoria and palermo. The paper also presents some of the works and everyday life of the prisoners of war.